ADMINISTRATIVE RESPONSIBILITY: ESSENCE AND SOME PROBLEMS OF TRANSFORMATION AT THE PRESENT STAGE - Гончарук, С. Т. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
The article deals with the perception of the nature of modern institute of administrative responsibility are the views of some scientists administratyvistiv relative concept and features of administrative responsibility, analyzed some problems of its transformation at the present stage and expressed some suggestions for improving the current administrative and tort law and practice.